2023
DOI: 10.3389/fpls.2023.1238624
|View full text |Cite
|
Sign up to set email alerts
|

Potential regulatory genes of light induced anthocyanin accumulation in sweet cherry identified by combining transcriptome and metabolome analysis

Yao Zhang,
Chaoqun Chen,
Yiling Cui
et al.

Abstract: Anthocyanins exist widely in various plant tissues and organs, and they play an important role in plant reproduction, disease resistance, stress resistance, and protection of human vision. Most fruit anthocyanins can be induced to accumulate by light. Here, we shaded the “Hong Deng” sweet cherry and performed an integrated analysis of its transcriptome and metabolome to explore the role of light in anthocyanin accumulation. The total anthocyanin content of the fruit and two of its anthocyanin components were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…When assessing the clustering of the CPDAGs, based on their SHD to all other CPDAGs, and the percentage of common directed edges (or directed and directed that turned into bidirected) with all other CPDAGs, it was found that in the transcriptomic case, this expectation was not satisfied (Figures 1 and A1). Indeed, in a transcriptomic analysis of quality changes during sweet cherry fruit development, the transcriptome of the organs has been found to exhibit strong differentiation depending on the developmental stage [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…When assessing the clustering of the CPDAGs, based on their SHD to all other CPDAGs, and the percentage of common directed edges (or directed and directed that turned into bidirected) with all other CPDAGs, it was found that in the transcriptomic case, this expectation was not satisfied (Figures 1 and A1). Indeed, in a transcriptomic analysis of quality changes during sweet cherry fruit development, the transcriptome of the organs has been found to exhibit strong differentiation depending on the developmental stage [50,51].…”
Section: Discussionmentioning
confidence: 99%